(untitled) (Health Renaissance, 2015)
Background: Dual-arch impression technique allows the simultaneous recording of tooth preparation, opposing anatomic tooth and maxillomandibular relationship. The accuracy of reproduction of this easy and quick technique, however, has not been studied in detail in past. Objective: To compare the accuracy of the impressions made by using the same impression material in dual arch plastic trays, dual-arch metal trays and acrylic resin custom trays. Methods: The dies obtained from the addition silicone impressions made in dual-arch plastic trays, dual-arch metal trays and full arch acrylic resin custom trays were compared for the dimensional accuracy with the prepared typodont tooth as a control. Student’s paired t-test and unpaired t-test were used for the data analyses using the Statistical Package for Social Studies (SPSS) version 11.5. Results: The dies obtained from all the impression combinations showed increased dimension (acrylic resin custom trays 9.4 mm±0.048, dual-arch plastic trays 9.5 mm±0.035, dual-arch metal trays 9.41 mm±0.017) as compared to the dimension of control (9.39 mm±0.007). Conclusion: All the tray-impression material combinations showed variable accuracies. Full arch acrylic resin trays resulted in greatest accuracy whereas dual-arch plastic trays the least accuracy. Health Renaissance 2014;12(2): pp: 111-117